Manajemen Strategi Biro Kepesantrenan Puteri: Meningkatkan Kinerja Pengurus untuk Masa Depan yang Gemilang: Management Strategy of the Women's Islamic Boarding School Bureau: Improving Management Performance for a Glorious Future - Moh Rofiki; Afifatur Rahmah; Eka Diana (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Islamic boarding schools face the challenge of adapting to globalization and digitalization without losing their traditional identity. This study aims to analyze the application of strategic management to improve the performance of administrators at the Bureau of Female Islamic Boarding Schools of Nurul Jadid Islamic Boarding School and to identify supporting and inhibiting factors. The research method uses a qualitative descriptive approach with a case study, where data is collected through participant observation, documentation studies, and in-depth interviews. Informants consist of the head of the bureau of female Islamic boarding schools, staff, and female Nurul Jadid Islamic Boarding School students. The selection of the research location is based on the ease of obtaining research data and the strategic role in the development of Islamic boarding school-based education, which is based on the research topic. Data were analyzed in three stages: reduction, display, and conclusion. The study results show that the stages of strategic management include formulation, implementation, and evaluation. Formulation involves formulating a vision and mission, SWOT analysis, and strategic goal planning. Implementation of the strategy consists of selecting administrators, providing leadership training, using digital applications for Islamic boarding schools, and giving appreciation to outstanding administrators. Evaluation is carried out through regular meetings to monitor progress and make strategy adjustments. Supporting factors include institutional leadership and inter-departmental coordination while inhibiting factors include limited time and funds. Implementing effective strategic management can improve the performance of administrators, support the achievement of the vision of the Islamic boarding school, and create an adaptive and competitive environment in the modern era.